2007
DOI: 10.1016/j.cellbi.2007.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐stromal transition of MMP‐7 immunolocalization in the rat ventral prostate following bilateral orchiectomy

Abstract: Epithelial cells from involuting rat ventral prostate (VP) express Matrilysin (MMP-7) mRNA. Herein, we investigated by immunohistochemistry the MMP-7 protein location and its association with tissue changes following castration in the VP. Normal and castrated adult male Wistar rats were sacrificed at different times after surgery. VP was examined by immunocytochemistry and immunoprecipitation. Castration promoted a shrinking of prostate ducts with an extensive stromal remodeling. In the VP from normal rats, MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
(55 reference statements)
1
14
1
Order By: Relevance
“…The prostatic stroma has been considered an important compartment due to its role in the maintenance of prostate histoarchitecture, homeostasis and its involvement in prostate diseases such as benign hyperplasia and cancer (Cunha et al, 2002; Chung et al, 2006; Ribeiro et al, 2006; Tuxhorn, 2002; Zhang et al, 2003). Our group has previously demonstrated a major role for the stromal components on prostate morphophysiology in several experimental conditions (Delella et al, 2007; Felisbino et al, 2007; Justulin et al, 2008, 2010; Vilamaior et al, 2000;). Thus, changes in the distribution of collagen fibers by cadmium treatment might affect normal epithelium–stroma interactions leading to changes in prostate homeostasis, which could be a factor in cadmium‐induced prostate carcinogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…The prostatic stroma has been considered an important compartment due to its role in the maintenance of prostate histoarchitecture, homeostasis and its involvement in prostate diseases such as benign hyperplasia and cancer (Cunha et al, 2002; Chung et al, 2006; Ribeiro et al, 2006; Tuxhorn, 2002; Zhang et al, 2003). Our group has previously demonstrated a major role for the stromal components on prostate morphophysiology in several experimental conditions (Delella et al, 2007; Felisbino et al, 2007; Justulin et al, 2008, 2010; Vilamaior et al, 2000;). Thus, changes in the distribution of collagen fibers by cadmium treatment might affect normal epithelium–stroma interactions leading to changes in prostate homeostasis, which could be a factor in cadmium‐induced prostate carcinogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…The importance of MMP7 for testicular integrity has been demonstrated by studies with transgenic animals overexpressing MMP7 [59], which presented disintegration of the testicular interstitial tissue and infertility. In the rat prostate, MMP7 is localized to the secretory granules of epithelial cells, but bilateral orchidectomy induces a change in MMP7 localization to the stroma just below the epithelium, suggesting that MMP7 can participate in the remodeling of the epithelial-stroma interface, probably by degradating components of the epithelial basement membrane [61].…”
Section: Discussionmentioning
confidence: 98%
“…The previous studies demonstrated that androgen exerts differential effect on expression of MMPs between normal and malignant prostate tissue ⁄ cells. For example, in vivo, both androgen ablation (Wilson et al, 1991;Powell et al, 1996;Wilson et al, 2002;Felisbino et al, 2007;Limaye et al, 2008) and androgen replacement (Wilson et al, 1991;Limaye et al, 2008) upregulates MMP mRNA and protein expression in rat ventral prostate. Moreover, in vitro studies using androgendependent prostate cancer LNCaP cells showed that androgen upregulates MMP-2 protein expression, without changes in MMP-9, and with TIMP-2 down regulation (Liao et al, 2003;Li et al, 2007), while androgen receptor signalling increases MMP-2 and MMP-9 activities in MDA cancer cell lines (Hara et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…, 2008). In a previous work, our group demonstrated using immunohistochemistry that after androgen ablation MMP‐7 localization changes from apical region of epithelial cells to the stromal space close to the basement membrane, suggesting that MMP‐7 participates in the epithelial‐stromal interface remodelling of the ventral prostate during the involution achieved by castration (Felisbino et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%